Knowledge and Perception on Sexual Harassment of Currently Working Women in Kathmandu Valley - Khanal, Prabha; Paudel, Manusha (Patan Prospective Journal, 2022)
Sexual harassment is a common and widespread phenomenon that has physical, emotional, and social consequences for individuals. The aim of this paper is to explore the knowledge and perception of sexual harassment among the working women in Kathmandu Valley. The systematic random sampling technique was used and selected 388 people working in the educational and non[1] educational sectors of the Kathmandu Valley. The result revealed that highest percentage of respondents have heard about the term "sexual harassment." low percent (83%) respondents had heard about SH in Bhaktapur compared to Kathmandu and Lalitpur (97%) and (86%), respectively. The majority of respondents (60%) stated that sexual harassment occurs in the workplace, as a result of misread signals from women. However, the majority of respondents (35%) stated that public transportation is the most risky place for sexual harassment followed by dark/ remote places (34%). Almost two-thirds of respondents (ranging from 62% to 65%) in all districts had heard about sexual harassment-related laws, acts, and policies, which was statistically significant at the 0.05 level. Similarly, respondents aged 35 and older had less knowledge than those in the younger age group, and this was significantly related to their age. The majority of respondents (93%) who worked in reception had the most knowledge of harassment-related laws and policies, followed by managerial supervisors (86%) whereas unskilled labor had lowest knowledge (47%) regarding these laws/ policies.